MLA 17-94 - Mineral Resource Investigation Of Eight Roadless Areas In Montana - Ronald B. Stotelmeyer (The National Institute for Occupational Safety and Health (NIOSH), 1994)
This report summarizes the U.S. Bureau of Mines evaluation of the mineral resources of eight roadless areas in several National Forests in Montana. The areas are amoung those that have been proposed as additions to the National Wilderness Presevation System In various sessions of the U.S. Congress. Mineral Commodities present include gold (lode and placer), silver, copper, lead, zinc, molybdenum, tungsten, rare-earth elements, fluorite, and barite. Numerous mineral deposit types occur. Past production was from gold placers and vein-type deposits. There is potential for development of large volume porphyry copper-molybdenum, disseminated gold, stratabound copper-silver, and exhalative massive-sulfide metallic deposits. A substantial increase in metal prices is needed before any known vein-type deposits will be economic.